Caries Risk Assessment in Children with Different Rates of Vitamin D Deficiency, Using Cariogram Model - Güler, Yasemin; Derelioğlu, Sera Şimşek; Yılmaz, Sinan (International Journal of Child Health and Nutrition, 2023)
Objective: Vitamin D plays a very important role in improving oral and dental health as well as general health. The present study aims to evaluate the risk of caries development risk of children with and without vitamin D deficiency using the Cariogram model. Methods: This study included a total of 75 healthy children aged 6-12 years, of which 50 (35 girls and 15 boys) had different levels of vitamin D deficiency, and 25 (12 girls and 13 boys) had none. Their risk of developing new dental caries was assessed with Cariogram. SPSS v21.0 (IBM, USA) was used for analyzing the study data. In the statistical tests, a p-value less than 0.05 was considered statistically significant. Results: Mean chronological and dental ages of the participants were obtained as 9±2.32 and 8±2.36, respectively. The distribution of salivary flow rate, buffering capacities, and distributions of Lactobacilli and S. mutans counts between the groups were found to be similar. There was a significant difference between Group I and Group II and between Group I and Group III in regard to the Cariogram green percentage (percentage of chances to avoid caries), p=0.002 and p<0.001, respectively. Conclusion: In the present study, we observed a decrease in the Cariogram green sector percentage with low levels of vitamin D and an increase with normal vitamin D levels. Therefore, chances to avoid new dental caries were increased in sufficient levels of vitamin D.